PRELIMINARY STUDIES FOR PRODUCING CRUDE LIPASE FROM TEMPE’S MOULD CULTIVATED IN RICE-HUSK-BASED SOLID MEDIA - Teuku Beuna Bardant; Kiky Corneliasari Sembiring; Achmad Hanafi Setiawan (Indonesian Journal of Chemistry, 2007)
The goal of these preliminary studies is to support Indonesian program for increasing palm oil added value through independent production technology based on Indonesian natural resources. Various palm oil derivatives could be synthesized enzymatically using lipase from microbes that available in Indonesia. Tempe's mould is available in abundance in Indonesia and had already been proved for producing lipase. This paper provides information about producing crude lipase from Tempe's mould cultivated in rice-husk-based solid media using palm oil as carbon source. Observed variables include solid media composition, optimum fermentation time, extraction and enriching process of crude lipase. The crude lipase was analyzed its hydrolysis activity on coconut oil and palm oil. The result of these preliminary studies shows that this production process is a simple and tough process and very potential to be developed.